Visuo-tactile interactions in the congenitally deaf: a behavioral and event-related potential study - Hauthal, Nadine; Debener, Stefan; Rach, Stefan; Sandmann, Pascale; Thorne, Jeremy D. (Frontiers in Integrative Neuroscience, 2015)
Auditory deprivation is known to be accompanied by alterations in visual processing. Yet not much is known about tactile processing and the interplay of the intact sensory modalities in the deaf. We presented visual, tactile, and visuo-tactile stimuli to congenitally deaf and hearing individuals in a speeded detection task. Analyses of multisensory responses showed a redundant signals effect that was attributable to a coactivation mechanism in both groups, although the redundancy gain was less in the deaf. In hearing but not deaf participants, N200 latencies of somatosensory event-related potentials were modulated by simultaneous visual stimulation. In deaf but not hearing participants, however, there was a modulation of N200 latencies of visual event-related potentials due to simultaneous tactile stimulation. A comparison of unisensory responses between groups revealed larger N200 amplitudes for visual and shorter N200 latencies for tactile stimuli in the deaf. P300 amplitudes in response to both stimuli were larger in deaf participants. The differences in visual and tactile processing between deaf and hearing participants, however, were not reflected in behavior. The electroencephalography (EEG) results suggest an asymmetry in visuo-tactile interactions between deaf and hearing individuals. Visuo-tactile enhancements could neither be fully explained by perceptual deficiency nor by inverse effectiveness. Instead, we suggest that results might be explained by a shift in the relative importance of touch and vision in deaf individuals.